From margins to mainstream : feminism and fictional modes in Italian women's writing, 1968-1990 - Lazzaro-Weis, Carol M., 1949- (University of Pennsylvania Press, 1993)
Carol Lazzaro-Weiss studies the fiction of twenty-five contemporary Italian women writers. Arguing for a notion of gender and genre, she runs counter to many Anglo-American and French feminist theorists who contend that traditional genres cannot readily serve as vehicles for feminist expression.
Keywords: Italian fiction -- Women authors -- History and criticism.; Italian fiction -- 20th century -- History and criticism.; Feminism and literature -- Italy.; Feminism in literature.; Roman italien -- 20e siècle -- Histoire et critique.; Féminisme dans la littérature.; LITERARY CRITICISM -- Feminist.; Feminism and literature; Feminism in literature; Italian fiction; Italian fiction -- Women authors; Italy; 1900 - 1999; Criticism, interpretation, etc.